Inhaled salbutamol from aerolizer and diskus at different inhalation flows, inhalation volume and number of inhalations in both healthy subjects and COPD patients. (21st April 2019) - Boshra, Marian S.; Almeldien, Ahmed G.; Eldin, Randa Salah; Elberry, Ahmed A.; Abdelwahab, Nada Sayed; Salem, Mohamed Nabil; Rabea, Hoda; Abdelrahim, Mohamed E. A.
Abstract: The aim of the present study was to demonstrate the effect of inhalation-flow, inhalation-volume and number of inhalations on aerosol-delivery of inhaled-salbutamol from two different dry powder inhalers (DPIs) in both healthy-subjects and chronic obstructive pulmonary disease (COPD) patients. Relative pulmonary-bioavailability and systemic-bioavailability of inhaled-salbutamol, delivered by Diskus and Aerolizer, was determined in 24-COPD patients and 24-healthy subjects. The healthy-subjects and the COPD-patients participated in the study for 7 days in which they received 4 study doses of 200 μg salbutamol (one slow-inhalation, two slow-inhalations, one fast-inhalation, and two fast-inhalations) in four alternative days with 24 hr washout period after each dose. Two urine-samples were collected from each study subjects. The first was provided 30 min post inhalation (USAL0.5), as an index of relative pulmonary-bioavailability, and the second was pooled to 24 hr post inhalation (USAL24), as an index of systemic-bioavailability. Fast-inhalation resulted in significantly higher USAL0.5 and USAL24 than slow-inhalation (p < 0.05) after one-inhalation in both healthy-subjects and COPD-patients but there was no significant difference between slow and fast-inhalation after two-inhalations. One-inhalation resulted in significantly higher USAL0.5 and USAL24 in healthy-subjects compared to COPD-patient at both slow and fast-inhalation (p < 0.05) except USAL0.5 with Diskus at slow-inhalation there was no significant difference. Also, two-inhalations resulted in significantly higher USAL0.5 and USAL24 compared to one-inhalation at slow-inhalation only (p < 0.05). No significant difference was found between Aerolizer and Diskus except in USAL0.5 of one slow-inhalation in both health-subjects and COPD-patients (p = 0.048 and 0.047, respectively). Device-formula relation is present at low inhalation-flow since Diskus resulted in significantly higher USAL0.5 and USAL24 in healthy-subjects compared to COPD-patient at slow inhalation than Aerolizer. It is essential to inhale-twice and as hard and deep as possible from each dose when using DPI especially with COPD-patients having poor inspiratory efforts such as elderly patients and children.